The 100 Most-Cited Research Publications on Servant Leadership: A Bibliometric Analysis - Dong Hu; Lei Mee Thien; Aidi Ahmi; Ahmed Mohamed (SAGE Open, 2023)
This study analyzed the 100 most-cited servant leadership publications in the Scopus database from 1991 to 2021 by using bibliometric analysis. The analysis includes visualization, bibliographic coupling, co-occurrence, and co-authorship analysis. Country contributions were examined, with the United States emerging as the dominant contributor, followed by the Netherlands, Australia, China, and Canada. van Dierendonck and Liden being the most influential contributors. Their work has focused on areas related to servant leadership scales, organizational behavior, and the conceptual development of servant leadership. The analysis of top keywords revealed a diverse range of research interests, underscoring the breadth and complexity of servant leadership as a concept. The study highlights the importance of international collaborations in advancing servant leadership research and emphasizes the need for increased research engagement from non-dominant countries to address the existing knowledge imbalance. The findings shed light on research trends, country contributions, influential authors, and important research themes, helping researchers identify gaps and future directions in servant leadership research. The findings could promote the development and application of servant leadership theory to enhance leadership practices and organizational outcomes.